TRANSLATION TECHNIQUES OF QUARRE TEKNIK PENERJEMAHAN PERISTIWA TUTUR BERTENGKAR FILM IP MAN 4: TEKNIK PENERJEMAHAN PERISTIWA TUTUR BERTENGKAR FILM IP MAN 4 - Emmanuela, Tasya Rezky; Adha, Kasa Rullah; Ayuningtias, Niza (Jurnal Analisis Pendidikan Sosial, 2024)
Film is one of the effective mass communication media in disseminating information that aims to convey messages to audiences that are shown in a story and then packaged with audio visuals. In conveying the message, a translation is needed, which shows that changing the grammatical form of the source language into the target language is an important part of translation in general. This study aims to find out what translation techniques are used by the translator to translate speech acts in quarreling speech events and to describe their impact on the shift in translation of speech acts in the movie Ip Man 4. This research uses descriptive method, which is a research method conducted by describing the object of research as it is with Translation Techniques that represent speech acts in quarreling speech events in Indonesian subtitles in Ip Man 4 movie. The Translation Techniques used by the translators to translate the speech acts. The result shows that the translator uses 13 translation techniques including modulation (25), literal (23), compensation (20), amplification (18), linguistic compression (8), adaptation (7), transposition (6), reduction (4), borrowing (3), variation (3), substitution (2), generalization (2), calcification (1). The dominant translation technique used is modulation translation technique. This is because the translation technique is applied by changing the point of view, focus or cognitive category in relation to the BSu. The change of viewpoint can be lexical or structural.